Azathioprine in autologous serum skin test positive chronic urticaria: A case-control study in a tertiary care hospital of eastern India - Dulal Chandra Bhanja; Loknath Ghoshal; Sudip Das; Suchibrata Das; Alok Kumar Roy (Wolters Kluwer Medknow Publications, 2015)
Context: Urticaria, also referred to as hives or wheals is a common and distinctive reaction pattern characterized by spontaneous eruption of wheals. About 30-50% of patients categorized as idiopathic urticaria have autoimmune urticaria, needing immunosuppressive agents. Immunosuppressive agents are either too costly or have serious side effects. Azathioprine seems to address both these issues, being less costly. Aims: The aim was to evaluate the role of azathioprine in autologous serum skin test (ASST) positive chronic urticaria (CU). Settings and Design: A single-blind randomized control trial of ASST positive patients of CU. Materials and Methods: Patients with positive ASST were allotted into two treatment groups, named group A and group B. Patients in group A were administered azathioprine (50 mg/day) for a period of 8 weeks and followed up till 36 weeks, while patients in group B were given placebo pills. All patients were directed to take levocetirizine (5 mg) on as and when basis, in addition. Urticaria was assessed by total severity score. Statistical Analysis Used: MedCalc statistical software (v 12.5 for Windows) to calculate P values in independent samples by t-test, Mann-Whitney test, Friedmann test, and ANOVA. Results: Administration of azathioprine in group A resulted in a significant diminution of the intensity of the disease as well as in the requirement of rescue antihistamine (positive primary and secondary outcome). Conclusion: Azathioprine not only had immunomodulatory properties during the treatment period, but also had lasting therapeutic effect as well. There were some gastrointestinal side effects in the initial stages but no incidence of hematological or biochemical disturbances.